Associations Between Specific Negative Emotions and DSM-5 PTSD Among a National Sample of Interpersonal Trauma Survivors. Issue 11 (June 2017) - Badour, Christal L.; Resnick, Heidi S.; Kilpatrick, Dean G.
The diagnosis of posttraumatic stress disorder (PTSD) has undergone several significant changes corresponding with the recent implementation of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders ( DSM-5 ). Many of these changes reflect a growing recognition that PTSD is characterized by a wide range of negative affective experiences that were underrepresented in prior conceptualizations of the disorder. The present study examined the prevalence and correlates of a new Criterion D symptom (D4-Negative Affect), which is aimed at assessing subjective problems with persistent negative emotion states (e.g., fear, anger, shame, guilt, horror) among a sample of 1, 522 U.S. adults with a history of interpersonal trauma recruited from a national online panel. The prevalence of D4-Negative Affect was very high among individuals with assault-related PTSD (AR-PTSD) and in particular, was significantly higher than among PTSD negative individuals. Moreover, specific problems with anger, shame, and fear were significantly and uniquely associated with AR-PTSD. Important differences also emerged as a function of gender and interpersonal trauma history. These findings provide initial empirical support for the expanded emphasis on assessing a wide range of negative affective experiences that may be associated with PTSD in DSM-5 .